Implementasi Pemeriksaan Atas Laporan Keuangan Pemerintah Daerah Oleh Badan Pemeriksa Keuangan Provinsi Sumatera Barat Pada Masa Pandemi Covid-19 - Mila Sri Suryani; Nurhazana Nurhazana (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2022)
This study aims to determine the implementation of the audit of local government financial statements by the BPK Representative of West Sumatra Province during the Covid-19 pandemic based on BPK Regulation No. 1 of 2017. This study also aims to determine the obstacles faced by the BPK Representative of West Sumatra Province in examining the financial statements of local government during the Covid-19 pandemic. This type of research is a mixed research method. Data collection techniques in this study were interviews, questionnaires, and documentation. The results showed that the BPK Representative Auditor for West Sumatra Province in examining the local government's financial statements, in general, was by BPK Regulation Number 1 of 2017 starting from the planning stage to the reporting stage. However, there are some technical differences in the implementation of the inspection carried out in 2020 from last year due to the Covid-19 pandemic. The differences that occurred at the West Sumatra Provincial Representative Office during the Covid-19 pandemic in reviewing local government financial reports from the planning, implementation, and reporting stages were carried out boldly. Obstacles faced by the BPK Representative of West Sumatra Province in examining local government financial statements during the Covid-19 pandemic, among others, difficulty obtaining data, limited interviews with auditees and related parties, relatively long document inspection, physical inspection, and limited goods checking.Keywords: Audit, Local Government, Financial Report